Valoración de impactos ambientales que causan las ladrilleras artesanales ubicadas en el caserío de Huayatán, distrito de Santiago de Chuco - Avila Esquivel, Kusy Betania (2023)
The general objective of this research is to evaluate the environmental impacts caused by draft bricks in the “Caserío de Huayatán”, Santiago de Chuco District, considering that currently the activities are carried out in draft mode, and there are no ecological technologies within the production processes. For this reason, this study is carried out with a descriptive observational methodology, based on interviews and surveys of the owners, workers and the population, taking as a sample four draft bricks and assessing the impacts on the environment through the Importance Matrix. For this, the environmental factors affected by the physical, biotic, perceptual, socio-economic and cultural environment are classified, therefore, manufacturing activities are classified into storage, transportation and operation of production processes. Obtaining the following results: 87% are detrimental impacts on the environment, and 13% are beneficial impacts, presenting the extraction of raw material and the firing of the brick at a level of critical importance. Coming to the conclusion that this manufacturing work is contributing to environmental pollution and the greenhouse effect, as well as affecting workers and the population, due to a series of measures of mitigation are presented to apply in the different production processes.